Carrier-envelope phase-dependent ionization of Xe in intense, ultrafast (two-cycle) laser fields. (30th November 2017) - Vasa, Parinda; Dharmadhikari, Aditya K; Mathur, Deepak
Abstract: We report an experimental study that shows the dependence of the tunnel ionization of Xe by two-cycle, intense, near infrared light on the carrier-envelope-phase (CEP) of incident laser pulses. At low values of the optical field ( E ), the ionization yield is found to be maximum for cos-like pulses; the CEP dependence of the ion yield becomes stronger for higher charge states. At higher E -values, the CEP dependence either washes out or flips. A simple phenomenological model is used to confirm that our results fall within the ambit of the current understanding of ionization dynamics in strong, ultrashort optical fields. In the observed tunnel ionization of Xe, CEP effects appear to persist for longer, eight-cycle, pulses. Electron rescattering is observed to play a relatively unimportant role in the observed CEP dependence. These results provide fresh perspectives in the ionization mechanisms of multielectron systems in the few-cycle regime.